LOWER CIRCULATING MIR-191-5P AND LET-7G-5P ARE INDEPENDENT BIOMARKERS OF RENAL INJURY. (April 2021) - Paradis, Pierre; Berillo, Olga; Huo, Ku -Geng; Fraulob-Aquino, Julio C.; Richer, Chantal; Briet, Marie; Boutouyrie, Pierre; Lipman, Mark L.; Sinnett, Daniel; Schiffrin, Ernesto L.
Abstract : Objective: Hypertension is associated with subclinical target organ damage including cardiac, vascular and kidney injury. Circulating microRNAs have been investigated as biomarkers of cardiovascular disease, but few studies have examined them as target organ damage biomarkers in hypertension. We aimed to identify circulating microRNAs that could serve as biomarkers of hypertension-induced target organ damage using an unbiased approach. Design and method: Normotensive subject, hypertensive patients (HTN) and patients with HTN associated with at least 2 other features of the metabolic syndrome (MetS) or with chronic kidney disease (CKD) grades 3–4 were studied (n = 15–16). Blood pressure was determined by automated office measurement (AOBP). Blood and urine were collected for determination of blood cell count, blood biochemistry and urinalysis. Platelet-free plasma (6 mL) was isolated from blood collected on EDTA, and RNA extracted for small RNA deep sequencing using Illumina HiSeq-2500. Differentially expressed (DE) genes were identified with a threshold of false discovery rate < 0.1. The most abundant DE miRNAs were confirmed by reverse transcription-quantitative PCR (RT-qPCR). Right common carotid artery remodeling and stiffness were assessed by ultrasound and aorta stiffness by carotid to femoral pulse wave velocity. Results: We found 4 up-regulated and 4 down-regulated miRNAs uniquely associated with the HTN group, 1 up-regulated uniquely associated with the MetS group, 1 up-regulated and 12 down-regulated miRNAs uniquely associated with the CKD group and 8 were found similarly DE in different groups (P < 0.01 and q < 0.1). Two down-regulated miRNAs, let-7g-5p and miR-191–5p of 11, the most abundant DE miRNAs, were validated by RT-qPCR. Correlation analysis revealed that let-7g-5p was associated with large vessel stiffening, miR-191–5p with diabetes, and both microRNAs with estimated glomerular filtration rate (eGFR) and inflammatory markers. Using let-7g-5p and miR-191–5p and parameters that correlated with eGFR as candidate variables, stepwise multiple linear regression generated a model showing that let-7g-5p, miR-191–5p and urinary albumin/creatinine ratio predicted eGFR with an adjusted R 2 of 0.40 (P = 1.1e-5). Conclusions: Circulating let-7g-5p and miR-191–5p were identified as independent biomarkers of chronic kidney disease among patients with hypertension, which could have pathophysiological and therapeutic implications.